Tafsir Konstitusional Pelanggaran Pemilukada yang Bersifat Sistematis, Terstruktur dan Masif - Ali, M. Mahrus; Rachman, Irfan Nur; Wijayanti, Winda; Putranto, Rio Tri Juli; Anindyajati, Titis; Asih, Putria Gusti (Mahkamah Konstitusi Republik Indonesia, 2012)
The Constitutional Court has created a legal breakthrough in handling the local head election dispute, in order to uphold the democracy and break away from habitual practice of systematic, structured, and massive (STM) violations. The Court does not simply calculate the results of vote count but also have to seek the justice and prosecute results counting rate that were disputed. As the juridical normative research, the research uses a statutory, case, historical approach and the sociology of law. The research shows that throughout 2008-2011 Court has granted the dispute for as many as thirty-two cases. Of that amount of cases, those with the STM violations are as many as 21 (twenty one) cases. Whereas the nature of TSM were divided into two kinds namely cumulative and alternative which both may cancel local head election results. There are three types of local head election violations, first, violation in the process that does not affect the results of the election. Second, the breach in the process that affect the election results, thirdly, violation of the terms of conditions to be a candidate which are principal in nature and can be measured. The systematic, structured and massive violation of the local head general election is violations committed by the structural apparatus, both government officials and election organizers, collectively; not an individual action, well-planned (by design) and the impact of such offencesis extensive rather than sporadic.